Demand for Fish in Urban Malawi: An Almost Ideal Estimation - Banda, Fredrick Mangwaya; Edriss, Abdi-Khalil; Jere, Wilson Wesley; Phiri, Horace (International Journal of Economics and Financial Issues, 2024)
There is a general consensus, among marketers, that dealing with competition requires their engagement with customers so as to build strong customer relationships. The purpose of this study is to find factors that influence the demand for various fish species caught and consumed in Malawi. Previous studies treated fish as a homogenous commodity even though there are different species of fish. This study is, therefore, the first to provide a disaggregated analysis of the demand for fish in Malawi employing primary data collected from the households in Blantyre city using a multistage stratified random sampling procedure. Results indicate that all the fish species used in the study, except matemba (Barbus paludinosus), are complementary and normal goods. Policy implications arising from this study are two-fold namely; policymakers need to make sure that people have more income to buy more fish and make sure that the price of fish does not just rise anyhow.